The Application of Hedging Accounting Procedures in Light of the Challenges of Cybersecurity CSC and its Impact on Reducing Capital Risk: An Applied Study in a Sample of Banks Listed on the Iraq Stock Exchange - Shaima Khattar; Nadia AbdelAbbas; Farah Khafaji (Penerbit Jurnal Indonesia, 2026)
The research aims to apply hedging accounting procedures in light of cybersecurity challenges (CSC) And explaining the impact of that in discount risks head Money , in addition to identifying the most important procedures that can be used to minimize the financial risks to which economic units are exposed by helping in Dealing with Cases that no maybe In it Prediction In the future on face certainty and that Risks Finance It arises from side Finance at the facility , and it increases with more Accreditation on Debts, The danger It represents Possibilities midwife For measurement To achieve losses or non Get on Value That because Risk They differ on non Confirmation where that The last not midwife For measurement. The research population consists of banks listed on the Iraq Stock Exchange, while the research sample was selected purposively from three banks, namely Bank Mosul For development Investment and bank Baghdad and bank via Iraq For investment, the research was conducted over a five-year period, from 2018 to 2022. The research reached a number of conclusions, the most important of which was that the application of hedging accounting procedures in light of cybersecurity challenges (CSC) whenever to a reduction risks head Money in banks is the research sample.